Technical and economic implications of fatal accidents in peruvian mining - Giraldo Paredez, Emiliano (2015)
The objective of this study is to promote the reduction of accidents in mining or other underground excavations, which in a greater percentage are caused by rockfall. On this occasion, an analysis of the technical and economic consequences of accidents is presented, then the factors with the highest incidence of accidents will be presented, as a result of the analysis of the information compiled from the sources. Due to the aforementioned, the primary sources have been used to collect the pertinent information on accidents that occurred in mining over more than 12 years. To meet the objectives of this publication, in addition, the existing literature has been reviewed and the costs of the accidents analyzed by Mg have been updated. Tomás Acero in 2004 and the social and business consequences. In general terms, the number of fatal accidents from 1970 to 2013 has been substantially reduced. 33% of fatal accidents are caused by rockfall. It is shown that for every fatal accident 28 incapacitating accidents occur, 138 minor and 2,822 incidents. A fatal accident would cost $ 397,895. Accidents caused by rockfall from 2000 to 2013 would have cost the mining industry $ 97,086,453, which translated into support would correspond to several kilometers of work carried out with rock bolts. Similarly, an accident has dire consequences for the victim's family, society and the company.